Les origines antiques d’un « art de la prudence » chez Baltasar Gracián - Karl Alfred Blüher (Astérion)
This article argues that the « art of prudence » recommended by Baltasar Gracián in his Oráculo manual revives the methods of the ancient Greeks and Romans who had been advocating an ars vitae and a tactical prudentia, which they often expressed as striking slogans, maxims and adages. Gracián’s « aphorisms » draw on the rich treasure of this pragmatic wisdom, adopting the features of a certain stoicism but also the cunning counsel praising « adaptation » and « dissimulation ». The components of this « art of prudence » belong to four different fields : philosophical works, in particular Seneca, Epictetus and Plutarch ; gnomic literature, such as the maxims of the Seven Sages or those of Publilius Syrus ; satirical writings, especially Martial and Persius ; and Tacitus’ political and moral thought.